INFLUENCE OF PSYCHOSOCIAL FACTORS IN DETERMINING THE CRIMINAL RESPONSIBILITY OF YOUNG OFFENDERS (I): PSYCHOSOCIAL IMMATURITY - Reyes Bedoya, Lilia Jacinta (2025)
This article critically reviews recent literature on how psychosocial immaturity and cognitive development influence the criminal responsibility of young offenders. Justice systems face the challenge of deciding whether to treat young people as adults or juveniles, highlighting the importance of understanding the factors that affect their ability to make decisions and assess the consequences of their actions. The review indicates that the cognitive and psychosocial skills necessary for mature decision-making continue to develop during late adolescence, supporting the need for differentiated approaches in the criminal treatment of young offenders. This analysis was based on a systematic review of literature published between 2012 and 2023, selecting peer-reviewed articles from databases such as PsycINFO, PubMed, and Google Scholar. The findings show that young people with psychosocial immaturity have difficulty foreseeing the long-term consequences of their actions. It is concluded that decision-making and self-regulation continue to develop until late adolescence, justifying a differentiated penal approach.